Modeling of Mineral Efficiency in Geothermal Hot Waters with Data Envelopment Analysis - Karaca, Zeki; Beigmohammadi, Elif Ozturk (Archives of Mining Sciences, 2025)
The Biga Peninsula is an important region of geothermal resources, heat mining in Western Anatolia. In this study, the modelling of mineral efficiency in hot waters was made with data envelopment analysis for the first time. Gold, silver, and lithium in the geothermal hot water were defined as the outputs, whereas physical properties of the geothermal resource such as temperature, pH level, electrical conductivity, and salinity were defined as the inputs. The output-oriented Charnes, Cooper, and Rhodes data envelopment analysis model, which measures the total efficiency, and the output-oriented Banker, Charnes, and Cooper data envelopment analysis model, which measures technical efficiency, were used in the study. A total of 50 models were created –25 with the first model and 25 with the second model – to analyse 21 geothermal resources in the Biga Peninsula. As a result of the analysis of the models, nine geothermal resources were found to have a relative efficiency of 100%. The average technical efficiency score in the Banker, Charnes, and Cooper model was 70%, whereas the average total efficiency score in the Charnes, Cooper, and Rhodes model was 68.5%. It was found that data envelopment analysis can be used to model geothermal resources in mineral operations.
Keywords: Modelling; geothermal; mineral economics; hot waters; mineral efficiency